2016
DOI: 10.1007/s00520-016-3323-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cancer diagnosis and treatment on employment, income, treatment decisions and financial assistance and their relationship to socioeconomic and disease factors

Abstract: Unemployment is a major driver of the financial impact of cancer. The costs of treatment may be particularly challenging for those with private health insurance who are more likely to be treated in the private health system where out-of-pocket costs are greater. Improved access to financial assistance is required to better avoid potential inequities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 23 publications
4
35
0
1
Order By: Relevance
“…In 2015, OOP expenditure in Australia was 20%, which was equal to the Organisation for Economic Cooperation and Development average (20%), but higher than the average paid in the UK (15%), New Zealand (13%), and Canada (15%) [21]. This is of concern, as it is known that people may delay or forgo healthcare due to costs [5,7]. Previous work by some of the authors found that 21% of Australian adults with cancer skipped care due to the costs [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, OOP expenditure in Australia was 20%, which was equal to the Organisation for Economic Cooperation and Development average (20%), but higher than the average paid in the UK (15%), New Zealand (13%), and Canada (15%) [21]. This is of concern, as it is known that people may delay or forgo healthcare due to costs [5,7]. Previous work by some of the authors found that 21% of Australian adults with cancer skipped care due to the costs [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by some of the authors found that 21% of Australian adults with cancer skipped care due to the costs [5]. In a survey of people with cancer, 10.9% indicated that the cost of treatment influenced their decision about cancer treatment [7]. A recent study using CancerCostMod identified that on average, Indigenous Australians with cancer had lower patient co-payments for MBS services and PBS prescriptions combined compared with non-Indigenous Australians with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the added benefit of employer-sponsored health insurance, paid employment has the potential to mitigate the financial stresses associated with cancer. 11, 12 Moreover, for women with breast cancer, employment could play a significant role in post-diagnostic health. Health benefits associated with employment include an increased sense of purpose, higher self-esteem, and a stronger sense of social support from others, all of which have been associated with improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Being diagnosed with a chronic disease can have a significant financial strain on the family, depleting the household's resources [45]. As healthcare costs continue to increase relative to household income, it will compete with basic household expenditure and cause financial hardship for families [46]. This situation might be worsened if a patient is unemployed or a family member has to reduce employment obligations as a result of caregiving responsibilities [47].…”
Section: Core Indicators Of Segmentationmentioning
confidence: 99%